Vibração de plantas de pimenta americana para produção de frutos em ambiente protegido - Freitas, Pâmela Gomes Nakada; Magro, Felipe Oliveira; Claudio, Marina de Toledo Rodrigues; Tavares, Ana Emília Barbosa [UNESP]; Cardoso, Antonio Ismael Inácio; Lanna, Natália de Brito Lima [UNESP] (FapUNIFESP (SciELO), 2015)
The aim of this research was to evaluate plant vibration for fruit and seed production of american pepper in greenhouse with open and closed sides. The experiment was carried out at Fazenda Experimental da Unesp/FCA located in the municipality of São Manuel-SP. Six treatments were carried out, in a split plot design, two plots with plant vibration or without plant vibration and three subplots with cultivars (‘Dirce’, ‘Dínamo’ and ‘Doce Comprida’). Plants were vibrated by shaking the wire where the stake was fixed, manually, for about 5 seconds, twice a day. Randomized block design with three replications were used. The same experiment was performed in two environments: with and without closed sides with screen. The traits evaluated were: mass of fruit and total and marketable number of fruits (no visible defects) per plant; percentage of marketable fruit; mass, diameter and length of the fruit; mass and number of seeds per fruit; and plant height. The fruit production was higher in the environment with sides closed, with 24 marketable fruits per plant whereas in the open environment, 7 marketable fruits. American pepper plant vibration did not affect production, length, diameter and average mass of the fruits. Exceptionally for the cultivar ‘Doce Comprida’, a higher seed production per fruit was obtained in open environment in the absence of plant vibration, in comparison to close environment, with average of 259 and 126 seeds per fruit, respectively. American pepper plant vibration did not affect production, length, diameter and average mass of marketable fruits.
Plant vibration of american pepper cultivars for fruit production in protected environment with and without closed sides
Keywords: Capsicum annuum; Fruiting; Shaking of plants